Penggunaan Media Puzzle untuk Meningkatkan Perkembangan Motorik Halus Anak Autis Kelas 1 di SLB Autis Harapan Mandiri Palembang - Arisandy, Desy; Lestari, Ayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Children with autism spectrum disorders often experience obstacles in fine motor development that impact the learning process, independence, and daily activities. This condition requires continuous mentoring and stimulation activities through learning media that are appropriate to the characteristics of autistic children. This community service activity aims to describe the application of puzzle media as an effort to stimulate the fine motor development of autistic children in grade I at the Harapan Mandiri Autism Special Needs School in Palembang. The community service implementation method is carried out through observation, mentoring, and direct practice of playing puzzles with students during the internship. The puzzle media used were animal-picture puzzles and finger-shaped puzzles that were adjusted to the children's abilities. The activity was carried out in three meetings over two weeks with the involvement of the class teacher as a mentoring partner. The results of the activity showed an increase in eye-hand coordination, finger movement accuracy, attention focus, as well as sitting endurance and independence of children in completing tasks. The conclusion of this community service activity shows that puzzle media can be used as an alternative stimulation media that is effective, applicable, and fun in supporting the fine motor development of autistic children in a special school environment.